PENGARUH MODEL PEMBELAJARAN CONCEPT SENTENCES UNTUK MENINGKATKAN KETERAMPILAN MENULISTEKS DESKRIPSI PADA SISWA KELAS X SMA NURUL IMAN TANJUNG MORAWA TAHUN PEMBELAJARAN 2021-2022 - Kesuma, Utami; Kusyani, Diah; Muliatik, Sri (Bahasa Indonesia Prima, 2023)
This study aims to determine the effect of the Contextual Teaching and Learning Learning Model on the Ability to Write News Texts for Grade VIII students of MTs Darul Arifin in the 2021-2022 Academic Year. The method used in this research is quasi-experimental. Sampling was carried out using a purposive sampling technique. The research sample consisted of 20 experimental and 20 control class students. Measurement of student learning outcomes based on research instruments in the form of subjective tests in the form of essays. Based on the results of data analysis, it can be concluded that there is a significant influence on learning outcomes in Writing News Texts using the Contextual Teaching and Learning Learning Model. This is shown from the results of the calculation of the posttest hypothesis test through the t-test at a significant level of 0.05, where tcount>ttable (2.864154 > 1.721296296). The achievement of the average student score in the Contextual Teaching and Learning learning class with a value of 84.25 reinforces this result. In contrast, conventional learning obtains a value of 79.5. These results indicate that student activities in the Contextual Teaching and Learning learning model are better.